2018
DOI: 10.3389/fendo.2018.00049
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Polysaccharide IV from Lycium barbarum L. Improves Lipid Profiles of Gestational Diabetes Mellitus of Pregnancy by Upregulating ABCA1 and Downregulating Sterol Regulatory Element-Binding Transcription 1 via miR-33

Abstract: Lycium barbarum L. (LBL) has beneficial effects on gestational diabetes mellitus (GDM) but the related mechanism remains unclear. Polysaccharides of LBL (LBLP) are the main bioactive components of LBL. miR-33, ATP-binding cassette transporter A1 (ABCA1) and sterol regulatory element-binding transcription 1 (SREBF1) affect lipid profiles, which are associated with GDM risk. LBLP may exert protective against GDM by affecting these molecules. Four LBLP fractions: LBLP-I, LBLP-II, LBLP-III, and LBLP-IV were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It also rose the high-density lipoprotein cholesterol and reduced the blood ester and malondialdehyde. LBLP IV had significant anti-diabetic activity on gestational diabetes mellitus [27]. The composition and function of LBPs are shown in Table 1.…”
Section: Active Ingredients 21 Lycium Barbarum Polysaccharidementioning
confidence: 98%
“…It also rose the high-density lipoprotein cholesterol and reduced the blood ester and malondialdehyde. LBLP IV had significant anti-diabetic activity on gestational diabetes mellitus [27]. The composition and function of LBPs are shown in Table 1.…”
Section: Active Ingredients 21 Lycium Barbarum Polysaccharidementioning
confidence: 98%
“…Interestingly, a significant decrease in the level of TNF‐α was detected in the L. barbarum treated group, but not in other adipokines, including adiponectin, leptin, and IL‐6 (Cai et al., 2015). Another study reported that the consumption of polysaccharides of L. barbarum (10 mg daily) during 4 weeks reduced insulin resistance, LDLc, total cholesterol, triglycerides, and malondialdehyde (MDA) and increased insulin release and HDLc in gestational diabetes mellitus patients (Yang et al., 2018). The mechanism of action evaluated in human pancreatic carcinoma cell SW1990 was related to an increase in ATP‐binding cassette transporter A1 and a downregulation of SREBP‐1c via miR‐33.…”
Section: Hypoglycemic and Hypolipemic Effect Of Lycium Barbarummentioning
confidence: 99%
“…In addition, although no directly evidence showed that miRNA-33 was involved in the treatment of DM-induced vascular dysfunction so far. Yang et al has shown that miRNA-33 acts as a key regulator in gestational DM of pregnancy ( 92 ). Thus, it is still worth for further exploration on the role of miRNA-33 in the effect of FGF21 on DM-induced atherosclerosis.…”
Section: Epigenetic Regulation Related To Fgf21 In Diabetic Vascular Complicationsmentioning
confidence: 99%